The description of the torment of the disbelievers in the Hereafter in the Qur'an - Syfa Fauzia Mustofa; Dadah Dadah (Gunung Djati Conference Series, 2021)
The purpose of this study is to discuss the description of the torment of unbelievers in the afterlife in the Qur'an. This research method uses qualitative research through literature study from secondary sources, namely theses and journals by applying content analysis as a tool to explore the collected data so that it can lead to conclusions. The results and discussion of this study include a general view of the meaning of infidels, descriptions of the afterlife and descriptions of the torment of infidels in the hereafter in the Qur'an. The conclusion of this study is that infidels are people who reject the truth that comes from Allah. During his life he did what he wanted. He feels that he will live forever in this mortal world, so he is desperately trying to get pleasure while in this temporary world. In the afterlife he will be held accountable for whatever actions he has committed while in this world. Allah has prepared a hell in which there is a blazing fire and a very painful punishment. This study recommends that a more holistic interpretation research be conducted.